Lean Startup as a New Way of Managing Technology Ventures Illustrated by the Example of Wlcome App - Magdalena Popowska; Patrycja Nalepa (Studia i Materiały)
The dot-com bubble in the 1990s made the technology industry aware that even excellent ideas backed by amazing teams are not sufficient to ensure a startup’s success. The biggest risk of startups is that they have to operate within many uncertainties, their market and customers are unknown, and their business model is not yet validated. Therefore, successful execution of such a venture requires a rigorous process that would validate different assumptions of the business idea. The Lean Startup method, introduced by E. Ries, gives the opportunity to eliminate some of the uncertainties and, therefore, to reduce the risks associated with starting a new business. Although this is not an easy method, as it requires minimum management knowledge and some analytical skills, it has become a highly recommended tool.